The Correlation Between Islamic Education and Islamic Law in Indonesia: A Systematic Literature Review - Mohamad Erihadiana; Muhammad Ridwan Aziz; Ayi Dini Purwandi; Dwi Haryanto Hamdani; Fardan Abdul Basith (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Islamic education in Indonesia functions not only as a means of transmitting religious knowledge but also as a medium for cultivating moral values, legal awareness, and social behavior within Muslim society. Specific Background Within Indonesia’s pluralistic legal and educational landscape, Islamic education and Islamic law coexist and interact across formal institutions, community settings, and national educational frameworks. Knowledge Gap Despite extensive scholarship on Islamic education and Islamic law as separate domains, their interrelationship in the Indonesian context has not been systematically synthesized. Aims This study aims to examine scholarly patterns, themes, and perspectives concerning the relationship between Islamic education and Islamic law in Indonesia through a Systematic Literature Review. Results The review of six studies published between 2024 and 2025 reveals that Islamic education serves as a primary channel for internalizing Islamic legal principles through formal instruction, character education, and ethical habituation, while Islamic law provides a normative foundation shaping curricula, pedagogical orientations, and moral objectives. The findings also indicate a reciprocal relationship that contributes to legal consciousness, ethical behavior, family legal knowledge, and sociocultural practices. Novelty This study offers an integrated synthesis that positions Islamic education and Islamic law as mutually reinforcing systems rather than isolated fields. Implications Strengthening their integration is essential for fostering moral integrity, legal awareness, and social harmony within Indonesia’s contemporary educational and sociocultural environment. Highlights: Islamic learning environments function as primary spaces for the internalization of normative legal principles. Normative legal frameworks guide curriculum orientation and ethical objectives within religious schooling. Reciprocal educational–legal interaction supports moral development and social cohesion in plural contexts. Keywords: Islamic Education, Islamic Law, Legal Awareness, Character Education, Systematic Literature Review